2017
DOI: 10.1007/s11250-017-1469-3
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus-1 (BHV-1), bovine leukemia virus (BLV) and bovine viral diarrhea virus (BVDV) infections in Algerian dromedary camels (Camelus dromaderius)

Abstract: This study was performed to investigate the presence of bovine herpesvirus-1 (BHV-1), bovine leukemia virus (BLV) and bovine viral diarrhea virus (BVDV) infections in dromedary camels (Camelus dromaderius) kept in mixed herds with sheep and goats in Algeria, since the prevalence of BHV-1, BVDV, and BLV infections among dromedary camels in Algeria is unknown. Totally, 111 camel sera were collected from two provinces (Laghouat and Ghardaia) in Algeria. The sera were analyzed for BHV-1 specific antibodies, BVDV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…In humans, the MERS-CoV and AHFV infections are known to be of high fatality rate (272)(273)(274)(275)298). Camel can also be infected by a number of other viruses (299)(300)(301)(302).…”
Section: Burnetii Still Neglected In the Oie List Of Zoonotic Pathmentioning
confidence: 99%
“…In humans, the MERS-CoV and AHFV infections are known to be of high fatality rate (272)(273)(274)(275)298). Camel can also be infected by a number of other viruses (299)(300)(301)(302).…”
Section: Burnetii Still Neglected In the Oie List Of Zoonotic Pathmentioning
confidence: 99%
“…The previous findings disagree with the findings of Saidi et al . [ 28 ] who found that the seropositivity rate was 9.0% for BVDV-specific antibody, although 41.4% of camels tested were positive for BVDV Ag. Moreover, the results agreed with a study of Wernery [ 29 ] who recorded that neutralizing antibodies was 11% to BVDV in Egypt, with a peak 23% in one area.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that camels might represent an important source for BVDV infection in all ruminants, including cattle, sheep, and goats breed in mixed herds since they had higher BVDV prevalence rates. Therefore, the prevention and control measures for BVDV spreading and persistence the camel should house in camel populations only to limit the spread of BVDV infection to ruminant populations [ 28 ]. The results of phylogenetic analysis of BVDV indicated that the isolated strain in this study was clustered with Sudan strain, proving the same source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…While this detection method has also been used for the screening of heterologous hosts for BVDV in various studies and has 100% agreement with a single‐tube‐time RT‐PCR in 764 samples from negative red deer, 125 formal evaluation has not been performed for heterologous hosts. In some studies, unexpectedly high numbers of ACE‐positive samples were detected: for example, 41.4% in Algerian camels with an overall seroprevalence rate of 9.0%; 6/84 (7%) in mule deer; and 22/440 (5%) in white‐tailed deer 122,126,127 . While these results suggest a high proportion of PI animals in the sampled populations, this conclusion is unlikely because the PI prevalence rate in cattle is generally below 1%.…”
Section: Infections In Heterologous Hosts: What Is the Importance Of mentioning
confidence: 94%